Spectroscopic Contrast of Diarylethene Molecules on Octanethiol Monolayer - Arramel, Arramel; Kudernac, Tibor; Katsonis, Nathalie; Feringa, Bernard Lucas; van Wees, Bart Jan (Makara Journal of Technology, 2017)
We present a systematic scanning tunneling microscopy (STM) study of bias-dependent imaging of disulfur diarylethene (2S-DE) molecules on octanethiol (C8) monolayer at room temperature. In a rigid confinement of the C8 matrix, we did not observe any significant variation in the appearance of the 2S-DE. On the contrary, a reversal in the apparent height of the 2S-DE was present when the molecule was situated on a gold vacancy island. We attributed this finding to the presence of a new electronic state that became accessible for a tunneling event. In addition, the C8 surface structure underwent a reversible phase transformation from √3 x √3 R30º hexagonal to c(4x2) square superlattice when the bias voltage was reduced from -825 mV to -425 mV or vice versa. Under a finite bias voltage, an appreciable topographic variation of the 2S-DE signature was demonstrated for the first time. This finding can be ascribed to a finite overlap of the associated wave functions that occurred between the tip state and the 2S-DE molecular energy level. We believe that physical insight on the bias-dependent imaging of organic molecules on solid surface is important towards the advancement of molecular electronics-based devices.